Disentangling the effects of plant species invasion and urban development on arthropod community composition. (16th April 2020) - Jesse, Wendy A. M.; Molleman, Jasper; Franken, Oscar; Lammers, Mark; Berg, Matty P.; Behm, Jocelyn E.; Helmus, Matthew R.; Ellers, Jacintha
Abstract: Urban development and species invasion are two major global threats to biodiversity. These threats often co‐occur, as developed areas are more prone to species invasion. However, few empirical studies have tested if both factors affect biodiversity in similar ways. Here we study the individual and combined effects of urban development and plant invasion on the composition of arthropod communities. We assessed 36 paired invaded and non‐invaded sample plots, invaded by the plant Antigonon leptopus, with half of these pairs located in natural and the other half in developed land‐use types on the Caribbean island of St. Eustatius. We used several taxonomic and functional variables to describe community composition and diversity. Our results show that both urban development and A. leptopus invasion affected community composition, albeit in different ways. Development significantly increased species richness and exponential Shannon diversity, while invasion had no effect on these variables. However, invasion significantly increased arthropod abundance and caused biotic homogenization. Specifically, uninvaded arthropod communities were distinctly different in species composition between developed and natural sites, while they became undistinguishable after A. leptopus invasion. Moreover, functional variables were significantly affected by species invasion, but not by urban development. Invaded communities had higher community‐weighted mean body size and the feeding guild composition of invaded arthropod communities was characterized by the exceptional numbers of nectarivores, herbivores, and detritivores. With the exception of species richness and exponential Shannon diversity, invasion influenced four out of six response variables to a greater degree than urban development did. Hence, we can conclude that species invasion is not just a passenger of urban development but also a driver of change. Abstract : This study assessed if two global, often co‐occurring threats to biodiversity—urban development and plant invasion—affect arthropod community composition in similar ways and to a similar extent. We detected that both factors influence arthropod communities, but do so differently. Urban development affected the taxonomic composition of arthropod communities through changes in species richness and diversity, while plant invasion increased arthropod abundance and caused significant taxonomic and functional biotic homogenization.